(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
Animals in the wild face numerous challenges to survive. One fundamental one is obtaining food, and to do so effectively, they must remember the places they have searched. Successfully completing this task requires a system of memory and attention. “Attention is understood as the mechanism that activates the processes involved in the processing of information, participates in and facilitates the work of all cognitive processes, regulating and exercising control over them.” (García, 1997; Rosello, 1998; Ruiz-Vargas, 1987). Attention is a selective process of receiving information that controls the threshold of our cognitive system and also fulfills alert functions, involved in educational and study learning processes, participates as an alert in high-risk professions, in the concentration and focus of research, memory and learning among others.